Evento municipal de música tradicional ecuatoriana. Propuesta de gestión cultural para el fortalecimiento de la identidad cultural en los jóvenes del cantón Arenillas, provincia de El Oro - Torres Cordova, Kevin Vinicio (2024)
Cultural management has always been an essential part of the development and maintenance of cultures; therefore, all forms of cultural expression of a country must be shared beyond the borders that limit the areas where they were founded. In this research, an artistic event was carried out, which allows as a general objective to contribute to the strengthening of cultural identity in the young people of the Arenillas canton of the province of El Oro, a place that is exempt from artistic activities inherent to the construction of their local identity. Regarding the field study, we worked with a population of three people who are authorities of the Decentralized Autonomous Government of the Arenillas canton to whom an interview was applied, the results of which allowed them to obtain relevant information about the current state of the canton about the cultural sphere, the same ones who stated that support is needed from the competent cultural entities, which allow the realization of events for the preservation of cultural identity. Therefore, in a universe of 351 young people from the Arenillas canton, through the application of surveys, showed an inclination for popular genres, since they tend to be more commercial. As a result, it became evident that traditional Ecuadorian music, being part of the cultural identity, is not to their liking. The Arenillas canton lacks events that contribute to consolidating traditional Ecuadorian music as part of the identity, the same situation that gave rise to the young people of the canton having a low level of acceptance of these types of musical genres. Therefore, the municipal traditional music event became an opportunity to instill in young people a love for the traditional genres of our country, which was reflected in the massive attendance of young people at the program. Keywords: cultural identity, cultural management, traditional Ecuadorian music, Arenillas canton